2012
DOI: 10.2478/v10117-012-0035-3
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Indonesia’S Creative Industries: Identification of People’S Characteristics and Creative Behaviour

Abstract: The purpose of this paper is to suggest an empirical model to assess personal characteristics and creative behaviour among creative workers in Indonesia’s creative industries. It is critical for people to do their best to ensure and realise that creativity is one of the most important elements in order to achieve high performance. Although a few previous studies have focused on the understanding of how the myriad of interacting potential creators can foster their performance, the characteristics and behaviour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…This result is confirm with the belief that the creative is a creative mindset of the actors which underlies the whole ideas (creative thinking) and action (creative action) in their life, not just how to get fresh ideas for making the design of posters, brochures or other promotional media meditative for example. Basis of creative thinking is so important, and its implementation in real terms in everyday life for career development, management ideas and promote the achievement of the creative people's performance, improving the welfare of even the achievement of the objectives of their higher life again [10].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This result is confirm with the belief that the creative is a creative mindset of the actors which underlies the whole ideas (creative thinking) and action (creative action) in their life, not just how to get fresh ideas for making the design of posters, brochures or other promotional media meditative for example. Basis of creative thinking is so important, and its implementation in real terms in everyday life for career development, management ideas and promote the achievement of the creative people's performance, improving the welfare of even the achievement of the objectives of their higher life again [10].…”
Section: Resultsmentioning
confidence: 99%
“…However, developing the ability to generate ideas is often touted in Art and Design programs as an outcome of undergraduate programs. Setiadi, Boediprasetya and Wahdiaman [10] educators are faced with the need to help students develop their creativity skills [4].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Creativity and innovation are not just vital features for organizations but also important for society economic development (Hitt, Ireland, Sirmon, & Trahms, 2011). Many studies had suggested that improving the creative performance of employees was an imperative stage if an organization wanted to achieve a competitive advantage in the dynamic society and technology (Amabile, 1988;Chen & Chang, 2013;Setiadi, Boediprasetya, &Wahdiaman, 2012). A number of approaches had been used to understand how creative workers shape the production of new ideas and the subsequent development of new ways based on their ideas.…”
Section: Introductionmentioning
confidence: 99%
“…Theresa Amabile has produced the most empirical research, exploring both personal characteristics and the interaction among people in the work environment. Other researchers considered the interaction process among workers and their personal and combined characteristics (Setiadi, Boediprasetya, & Wahdiaman, 2012;Hoban, 2002). Some authors considered the way groups interact to be the most important factor.…”
Section: Introductionmentioning
confidence: 99%